Young Activists in Catholic Groups. Meanings of Participation Across the Boundaries of the Religious Field - Genova, Carlo (Italian Sociological Review, 2022)
Most research about young people and religion in the Western context underlines their growing distance from institutionalised forms of religious participation, and explains it as a consequence of the weakness of their religious frames, as well as of other factors that interfere with the translation of these frames into forms of action. At the basis of this interpretation there is the hypothesis that these forms of participation are means of actualisation of religious values on the basis of religious beliefs and worldviews. Referring to recent research about young activists in Catholic groups in Italy, the article shows instead that their individual frames of involvement are variegated, and largely go beyond the boundaries of the religious field: religious factors are often not even considered as fundamental for collective identification, which is also rooted in shared non-religious distinctive meanings, practices and lifestyles.